Relationship between Dental and Oral Health Maintenance in Elders with the Occurance of Periodontitis (Case Study at the Posyandu Lansia RW 07 Gunung Anyar Tambak Village, Surabaya - Larasati Sekar Nagari; Ida Chairanna Mahirawatie; Ratih Larasati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Periodontitis is one of the most common periodontal diseases with an incidence of approximately 10% of adults worldwide. Periodontitis can lead to tooth loss, which has negative impact on chewing function, aesthetics and can affect the quality of life of the sufferer. High percentage of elderly with periodontitis in Posyandu Lansia RW 07 Gunung Anyar Tambak Village, Surabaya. The aim of the research was to determine the relationship between oral health maintenance of the elderly and the incidence of periodontitis in the Posyandu Lansia RW 07 Gunung Anyar Tambak Village, Surabaya. The type of research conducted was analytical research with a cross sectional method, with a sample of 35 elderly people at the RW 07 Posyandu Lansia, Gunung Anyar Tambak Village, Surabaya. The data collection instrument used is a questionnaire used to measure oral health maintenance and an examination sheet to identify periodontitis. The data analysis techniques using Spearman's rho. Conclusion : The average maintenance of oral health of the elderly in answering the research questionnaire was categorized as sufficient at 70.8%. Elderly people who experience periodontitis are 65.72%. There is a strong relationship between oral health maintenance and periodontitis.